HAZARD ANALYSIS AND CRITICAL CONTROL POINT (HACCP) PRODUKSI MALTOSA DENGAN PENDEKATAN GOOD MANUFACTURING PRACTICE (GMP) - Hermansyah, Muhammad; Pratikto, Pratikto; Soenoko, Rudy; Setyanto, Nasir Widha (JEMIS (Journal of Engineering & Management in Industrial System), 2013)
This study describes a series of treatment processes and functions of each stage in the production process and the conditions of maltose product with GMP parameters are implemented by the application of HACCP is equipped with Work Instructions CCP. The study was conducted with qualitative data analysis, by comparing the data and the results of observations with the relevant literature, in the form of articles, research journals, and generally accepted standards, although the calculation of GMP with some quantitative data. Through the resulting composition of the seven studies document the HACCP assessment, include: (1) Establishment of HACCP team, (2) Description of Products and Processes, (3) Purposes and Consumer Products, (4) Process Flow Diagram, (5) Hazard Identification, (6 ) Determination of the CCP, and (7) Worksheet CCP. Documents 1, 2, and 3 have been prepared to review and revise the existing old documents, while the documents 4 to 7 is a new document. The seven documents is then also equipped with Work Instruction documents CCPs to facilitate labor in monitoring and control of critical control points (CCPs). The results showed maltose production process generally consists of four main phases, including: likuifikasi, saccharification, purification (filtration and ion processes), and concentration.